Addressing maternal mortality in selected Districts of Madhya Pradesh, India - A human rights-based approach - Manju Toppo; Dinesh Kumar Pal; Devendra Gour; Veena Melwani; Amreen Khan; Soumitra Sethia (Wolters Kluwer Medknow Publications, 2019)
Background: Maternal mortality is an indicator of state of maternal health services, status of women, women's health, and above all developments of nation. Objectives: The objectives of the study were to identify the patterns and causes, medical as well as sociocultural, of maternal death as well as consider and list out the rights realization perspective of the mothers, their immediate families and the community at large. Materials and Methods: A cross-sectional study was conducted in three districts of Madhya Pradesh, India, for 1 year. One hundred and two maternal deaths were covered, and verbal autopsy was conducted. Human right perspective was assessed using questionnaire. Results: Majority (64.7%) of maternal deaths occurred between 18 and 25 years of age. About 50.9% were primigravida, and postpartum hemorrhage was the most common cause. Nearly 53.9% had visited more than one facility before death. Conclusion: Poor antenatal care and lack of human resources posed major reasons for death in all facilities. Rights realization among the beneficiaries was found to be very poor.